School Principals’ Experiences in Building Trust - Abdullayev, Shakir (ADA University, 2024)
This research aims to study the experiences of school principals in building trust. Particularly, the research has focused on principals and teachers of public and private schools. The research has aimed to find out how principals and the teachers defined the term trust within their educational institutions. Consistent with the theories and the gap in the local literature, a qualitative research approach has been practiced within public and private schools in Baku, Azerbaijan. The following research questions have guided this research: “How do the principals and the teachers define the term “trust”?” and “What practices do school principals employ to build trust with teachers?”. This study subsidized the new information regarding trust which created awareness while learning the experiences of the Azerbaijani school principals and the teachers. While researching the new experiences, this study helped to learn the importance of addressing trust in the principal-teacher dynamic. The findings showed that principals had three main sub themes in building trust at school: 1) Exercises in Empathy, 2) Relates to Teachers as Persona, 3) Creates Experiences of Voice and Choice. The study concludes for potential implications of building trust for principals in educational leadership for the further studies.
Keywords: Teachers -- Azerbaijan -- Baku -- Attitudes; Educational leadership -- Azerbaijan -- Baku; Interpersonal trust -- Educational settings.; Educational leadership; Education